Representation Theorems for Integrated Semigroups - Vugdalić, Ramiz (Sarajevo Journal of Mathematics, 2024)
In this paper $\left( S(t)\right) _{t≥ 0}$ is an exponentially bounded integrated semigroup on a Banach space $X,$ with generator $A.$ We present some relations between an integrated semigroup and its generator $A,$ or its resolvent. 2000 Mathematics Subject Classification. 47D60, 47D62